An orthonauplius of 'Orsten'-type preservation from the Upper Cambrian (Furongian) of South China - Zhang, Huaqiao; Dong, Xi-ping; Waloszek, Dieter; Maas, Andreas (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen, 2016)
A tiny larva of. 'Orsten'-type of three-dimensional preservation has been recovered from the Upper Cambrian Bitiao Formation of Wangcun section, western Hunan, South China, herein interpreted as an orthonauplius stage of a crown-group crustacean. The specimen comprises an ovoid body with a prominent labrum and three pairs of appendages. In all it exhibits comparable morphological similarities with the type-A larvae described earlier from other. 'Orsten'-type deposits. The new orthonauplius can be considered to represent a new form of type-A larvae. Such larvae represent a morpho-type and were previously reported from the Cambrian palaeo-microcontinents Laurentia, Baltica, and Australia; their find now also from South China implies a pandemic distribution. With this, type-A larvae have the widest and longest-lasting record of all Cambrian crustaceans, possibly even euarthropod fossils described so far.